Exploring PMOs through community of practice theory - Aubry, Monique; Müller, Ralf; Glückler, Johannes (Project management journal, 2011)
This article explores project management offices (PMOs) through community of practice theory. Preliminary results from a national health care case study are used to confirm the legitimacy of this approach. Today's knowledge-based economy calls for mechanisms to share knowledge. The issue of making more with less is at stake in order to reuse good practices, support innovative practice, and prevent the reinvention of the wheel. Members of these communities are at the heart of the learning process. The originality of this research is that it sheds light on PMOs in a new theoretical perspective within the field of knowledge management.